What Should Critique Do? On the Three Interpretations of Transcendental Philosophy - Paweł Korzeb (Cosmos and History: The Journal of Natural and Social Philosophy, 2026)
This paper examines three main ways of interpreting transcendental philosophy—metaphysical, psychological and epistemological—to investigate their significance for contemporary thought. I aim to show that different views of critical philosophy depend on how the ontological status of the transcendental conditions of possible experience is determined. In metaphysical interpretations, the transcendental refers to the metaphysical sphere of becoming or manifestation constituted by the activity of the subject or nature; in psychological ones, to the functions, capacities and faculties of the mind; and in epistemological ones, to the necessary norms or principles of scientific knowledge. The three interpretations oscillate between two models of critique, reflected in two naval metaphors that Kant used to illustrate his philosophy. In the model of the island of certainty, critical philosophy searches for necessary and immutable conditions of objects, functions of the mind or norms of rationality. In the model of navigation of the uncertain sea, critical philosophy aims to orient thinking to avoid extremes of dogmatism and scepticism. I will argue that since the concept of conditions of experience was subject to objections proving their contingency and revisability, the model of the island of certainty is untenable. However, the transcendental method could help us avoid dogmatism and scepticism in our approach to metaphysical discourse, cognitive science and the implications of scientific discourse for our self-understanding. In short, the aim of transcendental philosophy is to navigate the changing meanings of the ideas of metaphysical ground, mind and rationality.